An improved procedure based on fluorescence immunochromatography for rapid detection of group B streptococcus from enrichment cultures - Xiaoli Chen; Sijia Cao; Yan Ni; Xinyi Chen; Yu Qiu; Mingjing Zhang; Jianguo Fu; Lijuan Zheng; Zimin Tang; Huiming Ye (BMC Pregnancy and Childbirth)
Abstract Background Group B streptococcus (GBS) is a major cause of perinatal infectious morbidity and mortality. Although intrapartum antibiotic prophylaxis (IAP) administration for ≥ 4 h is effective in preventing neonatal early-onset GBS diseases, the conventional culture-based approach to identify GBS often takes 24–72 h. This study aimed to find a strategy to improve the efficacy of GBS screening. Methods We developed a fluorescence immunochromatographic test (FICT) strip to detect GBS within 15 min. The detection limit, analytical sensitivity, cross-reactivity and performance of the strip were evaluated. The performance of the strip on vaginal-rectal swabs with or without enrichment culture was compared with real-time quantitative polymerase chain reaction (qPCR) and colloidal gold immunochromatography (GIC) assay with conventional enrichment culture method as the reference method. Results The detection limit of the strip ranges from 104 CFU/mL to 106 CFU/mL. Additionally, the strip has detected all of the positives from 48 h enrichment cultures (175/175). and 30 GBS strains representing different serotypes at cell density of 106 CFU/mL yielded positive results. Cross-reactivity test indicated no false-positive results. The sensitivity on direct samples was 34.48%, while 4 h enrichment in LIM broth prior to FICT has greatly increased the sensitivity to 90.91% with the specificity being 95.35%. Conclusions The improved procedure based on the FICT for GBS detection from short-term LIM broth cultures was expected to guide IAP administration in obstetrical emergencies.